Hibah Orang Tua Kepada Anak Perempuan Dihitung Sebagai Bagian Warisan - Wahidah, Wahidah (IAIN Antasari Banjarmasin, 2014)
This study is motivated by the facts on the field that there are many cases of family on the practice of the grants from parents to daughters. From the study on six cases on the practice of parentsâ grants to their children, it is concluded that all of the grants given to the children can be categorized as grants in the general terms since they are in the forms of pure grants or will. From the perspective of Islamic law, this practice still can be justified since it is in accordance with faraidh and grants concept in Islam.